Environmental factors affecting larval fish community in the salt marsh area of Guadiana estuary (Algarve, Portugal) - Gonçalves, Renata (2018)
Salt marsh areas in the Guadiana estuary are important nursery sites for many fish species of commercial and recreational value. More effective protection measures should be adopted as the area is highly affected by anthropogenic and natural threats. Studying larval fish communities in these impacted nursery areas will be relevant to the management of local ecosystems and to larval fish ecology in general. Spatial and seasonal distribution and the effect of environmental factors on the larval fish community of this ecosystem were studied for one year (April 2010 to March 2011). Larvae were sampled monthly in parallel with phytoplankton and zooplankton. Hydrological data and physical parameters were monitored. A decision tree model was used to assess the influence of environmental factors on the larval fish community. A total of 130 larvae and 1171 eggs were caught. Diplodus sargus, Sardina pilchardus, and Pomatoschistus microps were the most abundant larval fish species. The peaks of fish larvae abundance occurred in March and April. The output of the model demonstrates that the abundance of larval fish is determined by the abundance of eggs, zooplanktonic food, and water flood and flow. This study shows the importance of the Guadiana salt marsh as an area for fish nursery and highlights the need for conservation of this area.